2018
DOI: 10.21315/jcdc2017.22.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Discrepancies between Design and Construction in the Pakistan Construction Industry

Abstract: Abstract:In building construction, discrepancies frequently occur between design and construction in relation to architectural details, structural details, materials, and quality of construction. The objective of this paper is to identify the major causes of discrepancies in building construction. A questionnaire was utilised that contained 65 potential causes of discrepancies classified into 4 categories: design, tendering, construction, and overall project. The data was from Pakistan and the response rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
(28 reference statements)
0
11
0
1
Order By: Relevance
“…According to the State Bank of Pakistan (SBP), published industry surveys estimate that the residential real estate industry has a current value of about $700 billion. Real estate and construction, together, account for approximately two percent of Pakistan's total GDP (Choudhry et al, 2017).…”
Section: Market Competitiveness and Transaction Transparency In Pakistanmentioning
confidence: 99%
“…According to the State Bank of Pakistan (SBP), published industry surveys estimate that the residential real estate industry has a current value of about $700 billion. Real estate and construction, together, account for approximately two percent of Pakistan's total GDP (Choudhry et al, 2017).…”
Section: Market Competitiveness and Transaction Transparency In Pakistanmentioning
confidence: 99%
“…The construction assembly methods and construction details play a vital role in ensuring building durability. The systemic coordination of modular construction could potentially overcome the issues of construction methods in many post-disaster reconstruction projects (Miyamoto et al, 2011) and minimise the discrepancies between design and construction (Choudhry et al, 2018).…”
Section: Development Of Modular Design Criteriamentioning
confidence: 99%
“…It has also been observed that although this problem has been argued and questioned for about 20 years, it persists. Choudhry, Gabriel, Khan, and Azhar () warn that this lack of interaction still occurs, and that the most common changes are due to owners requesting design changes due to financial problems and lack of skilled labor in the construction market.…”
Section: Construction Site Sustainabilitymentioning
confidence: 99%